Combination Therapy With Anti-PD-1 and Anti-B- and T-lymphocyte attenuator Results in a Synergistic Therapeutic Effect Against Murine Glioblastoma. (1st September 2019) - Choi, John; Saleh, Laura; Pant, Ayush; Routkevitch, Denis; Tong, Luqing; Kim, Young-Hoon; Xia, Yuanxuan; Jackson, Christopher Mitchell; Jackson, Christina; Lim, Michael
Abstract: INTRODUCTION: The immune checkpoint molecule programmed cell death protein-1 (PD-1) has been the mainstay target of immunotherapy. However, the recent CheckMate 143 trial involving antibodies against PD-1 (anti-PD-1) failed to meet its primary endpoint of improved overall survival in patients with glioblastoma (GBM). In part, this issue may be due to the expression of alternative checkpoints such as B- and T-lymphocyte attenuator (BTLA) on several immune cell types, including cytotoxic and regulatory T cells. Several murine GBM models such as GL261 and CT2A indicate that there is significant upregulation of BTLA in tumors with associated T cell exhaustion. We investigate the use of antibodies against BTLA and PD-1 on reversing immunosuppression and increasing long-term survival in a murine GBM model. METHODS: C57BL/6 J mice were implanted with the murine glioma cell line GL261 and randomized into 4 arms: (i) control, (ii) anti-PD-1, (iii) anti-BTLA, (iv) anti-PD-1 + anti-BTLA. Kaplan-Meier curves were generated for all arms. Additionally, flow cytometric analysis of blood and brains were done on days 7 and 16 post-tumor implantation. RESULTS: Tumor-bearing mice treated with dual anti-PD-1 and anti-BTLA therapy experienced improved overall survival (75%) compared to anti-PD-1 (25%) or anti-BTLA (0%) alone ( P  = .008). Compared to monotherapy arms, mice treated with combination therapy also demonstrated increased levels of CD8 + cytotoxic T cells as well as decreased levels of CD4 + Foxp3 + regulatory T cells on day 7 in the blood and day 16 in the brain ( P  < .05). CONCLUSION: This is the first preclinical investigation into the effects of combining anti-PD-1 and anti-BTLA treatment in GBM. We also show a direct effect on integral immune cell populations such as anti-tumor CD8 + T cells and immunosuppressive regulatory T cells through this dual therapy.